Introduction of a Simplified Psoriatic Arthritis Magnetic Resonance Imaging Score (sPsAMRIS): A Potential Tool for Treatment Monitoring in Peripheral Psoriatic Arthritis - Daniel B. Abrar; Christoph Schleich; Ralph Brinks; Christine Goertz; Miriam Frenken; Matthias Schneider; Sven Nebelung; Philipp Sewerin (Diagnostics, 2020)
Background: To evaluate whether a simplified (s) version of the psoriatic arthritis magnetic resonance imaging score (PsAMRIS), sPsAMRIS, is a potential tool for therapy monitoring in psoriatic arthritis (PsA). Methods: Seventeen patients with active psoriatic arthritis (PsA) underwent magnetic resonance imaging (MRI) at 3 T of the clinically dominant hand at baseline and after 6 months. Scoring was performed by two musculoskeletal radiologists in terms of the PsAMRIS and sPsAMRIS, which is a simplified version with reduced item numbers based on prior evaluation of responsiveness to change by standardized response means (SRMs). Both scores were compared by calculation of overall and each sub-score’s SRMs and relative efficacy (RE) after bootstrapping. Results: PsAMRIS sub-scores of MCP joints 3 and 4, and proximal interphalangeal (PIP) joint 4 had the highest SRM (−0.07 each), indicating highest responsiveness to change, and were, therefore, included in sPsAMRIS. Compared to PsAMRIS, sPsAMRIS was characterized by higher SRMs (sPsAMRIS: −0.13 vs. PsAMRIS: −0.02) and higher RE (29.46). sPsAMRIS and PsAMRIS were highly correlated at baseline (r = 0.75, p < 0.01 (Pearson’s correlation)) and at 6-month follow-up (r = 0.64, p = 0.01). Mean time burden for completion of scoring per MRI study was significantly reduced when using PsAMRIS (469 ± 87.03 s) as compared to sPsAMRIS (140.1 ± 21.25 s) (p < 0.001). Conclusion: Due to its similar responsiveness to change compared to standard PsAMRIS, and time efficiency, sPsAMRIS might be a potential diagnostic tool to quantitatively assess and monitor therapy in PsA.